Case Report: First-Line Immunotherapy for Esophageal Squamous Carcinoma Combined With Hypopharyngeal Squamous Carcinoma Yields Sustained Survival Benefit - Yang, Yi; Liu, Xiangliang; Song, Wei; Lu, Jin; Yin, Na; Ye, Xiaojun; Chen, Xiao (Frontiers in Immunology, 2022)
Esophageal cancer, as one of the most common malignant tumors in the upper gastrointestinal tract, is highly invasive, with poor prognosis and low 5-year survival rate. Hypopharyngeal cancer has a low incidence among head and neck malignant tumors, but its prognosis is poor and it is prone to recurrence, and because the upper respiratory tract has similar tissue types as the upper gastrointestinal tract, it is prone to the second primary tumor of the upper gastrointestinal tract, however, such patients with double primary carcinoma are uncommon in the clinic, and most of them are already advanced at the time of diagnosis, losing the chance of surgical resection, with poor results and poor prognosis after radiotherapy treatment, therefore, the choice of treatment strategy for such inoperable resectable patients is still a great challenge for clinicians.In this case, we report a patient with a double primary esophageal squamous carcinoma combined with hypopharyngeal squamous carcinoma without family history of tumor, who achieved complete remission after first-line chemotherapy combined with immunotherapy, with both lesions shrinking and the hypopharyngeal tumor disappearing. The survival benefit was ensured at the same time.